Determination of Neutron Flux of Isfahan ZPR in Different Level of Energy by MCNP COD for Investigate of BNCT - Eghbali Borujeni Akram (Journal of Global Pharma Technology, 2018)
Relating to deaths caused by cancers, we have tried to investigate the type of the cancers, and common method used for their treatments. Then we have evaluated the advantage and disadvantage of different methods, in regarding with the type of cancers, aiming to proof, that BNCT method can be the most appropriate methods for treatment of cancer in comparison with the other methods available. Now of days, advanced method of BNCT use a thermal (E n < 0.5 eV), or epithermal (0.5 eV < E n < 10 keV), neutron beam in conjunction with tumor- targeting boron compound for irradiation of glioblastoma and metastatic melanomas. In conjunction with, a systematic Mont carlo N-particle (MCNP) investigation of the different level of energy for neutron in ZPR (Zero Power Reactor) has been performed.  We did calculated with MCNP code, on neutron flux in ZPR, for different level of energies, and to complete the work, we compared the results with neutron flux requirements in BNCT cancer treatments. We believe that in future, BNCT can pursue its way as one of the safest and fastest method of brain cancers treatment, and we hope that in the near future, an appropriate (bed) will be established, for research and development of this method in our country, so that this method can become Vastly available to those patients, who are hopelessly seeking, a safer methods of brain cancer treatment.  Keywords: BNCT, Cancer therapy, Neutron source, Neutron flux, MCNP, ZPR.